THE QUALITY OF ISA BROWN CHICKEN EGGS AGED 100-104 WEEKS GIVEN COMMERCIAL RATIONS WITH ADDITIONAL SEASHELL FLOUR - F., Aziz; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - AgustusDO - 10.24843/JPT.2020.v08.i02.p07, 2020)
This study aims to determine the quality of Isa Brown chicken eggs aged 100-104 weeks which were given commercial rations with additional seashell flour. The study was conducted in Pesedahan Village, Manggis District, Karangasem, Bali, and lasts for 4 weeks. The design used was a Completely Randomized Design (CRD) with 4 treatments and 5 replications, and each test used 5 chickens. The treatment given is; commercial rations without the addition of seashell flour (A), commercial rations with an additional 1% of seashell flour (B), commercial rations with an additional 2% of seashell flour (C), commercial ration with an addition of 3% seashell flour (D). The variables observed were egg weight, egg index, egg shell weight, egg shell thickness, Haugh Unit, egg pH, and egg yolk color. The results of this study indicate that the provision of commercial rations with the addition of 1%, 2% and 3% seashell gives statistically not significantly different results (P> 0.05) on egg weight, egg index, egg shell weight, shell thickness eggs, Haugh Unit, egg pH and egg yolk color compared with the control treatment (A). Based on the results of this study it can be concluded that the administration of seashell flour with 1%, 2% and 3% in Isa Brown chicken aged 100-104 weeks has no effect on egg quality which includes egg weight, egg index, egg shell weight, egg shell thickness, Haugh Unit, egg pH and egg yolk color and have not been able to improve egg quality in egg yolk while egg quality in egg weight, egg index, eggshell weight, egg shell thickness, Haugh Unit, and pH still have good quality. keywords: egg quality, seashell flour, isa brown